2012
DOI: 10.1111/j.1600-0722.2012.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior and posterior neck muscle activation during a variety of biting tasks

Abstract: Bruxism may be involved in the aetiology of myofascial neck pain. The objective of this study was to test the hypothesis that anterior and posterior neck muscles co-contract during jaw clenching. Ten test subjects developed different feedback-controlled submaximum bite forces in a variety of bite-force directions by means of bite-force transducers. The electromyographic activity of the sternocleidomastoid and supra/infrahyoidal muscles, and of the semispinalis capitis, semispinalis cervicis, and multifidi musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…Recent intramuscular EMG studies have shown that, for an upright body position, individual superficial and deep neck muscles co‐contract at 10% to 15% of their maximum voluntary contraction (MVC) during a variety of controlled jaw‐clenching tasks at submaximum force (ranging from 50 to 300 N) . This activation level corresponds well to those found during mastication.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recent intramuscular EMG studies have shown that, for an upright body position, individual superficial and deep neck muscles co‐contract at 10% to 15% of their maximum voluntary contraction (MVC) during a variety of controlled jaw‐clenching tasks at submaximum force (ranging from 50 to 300 N) . This activation level corresponds well to those found during mastication.…”
Section: Introductionmentioning
confidence: 64%
“…This activation level corresponds well to those found during mastication. Another interesting finding for several neck muscles is the occurrence of low‐level, long‐lasting tonic activation (LLTA) which outlasts the specific submaximum motor tasks . LLTA of motor units (also known as Cinderella units) has been observed in previous studies of neck muscles, and it has been hypothesised they might be a source of muscle lesions or fatigue in neck pain patients .…”
Section: Introductionmentioning
confidence: 98%
“…In humans, Wang et al (2004) reported increased cervical muscle EMG recorded from sternocleidomastoid muscles following noxious injection into the masseter muscle. Evidence of this inter-relationship is also seen by increased activation of both anterior and posterior superficial, and deep cervical muscles during maximal and submaximal clenching (Lodetti et al, 2012;Hellmann et al, 2012;Giannakopoulos et al, 2013a;2013b). Based on this evidence, reduction in upper cervical mobility may be explained by activation of masticatory (Torisu et al, 2007;Manfredini et al, 2013) as well as cervical muscles during conscious teeth contact (Giannakopoulos et al, 2013b).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 89%
“…Increased anterior and posterior superficial, and deep neck muscle activity has been recorded during conscious teeth clenching (Hellmann et al, 2012 ;Giannakopoulos et al, 2013a;Giannakopoulos et al, 2013b).…”
Section: Introductionmentioning
confidence: 96%
“…This leads a variety of neuromuscular interactions, for instance, synchronized extension–flexion movements of the head during jaw-opening/closing cycles [7]. …”
Section: Introductionmentioning
confidence: 99%